Longing for Health: a Practice of Religious Healing and Biomedicine Compared - Vellenga, Sipco J. (Journal of religion and health, 2008)
The standard notion is that biomedicine and religious healing are two completely different practices in modern Western societies. In this article, this notion is questioned by comparing in the Netherlands one practice of religious healing, namely the Services of salvation and healing' of the Pentecostal Levensstroom gemeente (Livingstream Church) of Jan Zijlstra, and one practice of biomedicine, namely the Antoni van Leeuwenhoek Cancer Hospital (AvL). What are the differences and possible similarities between these two? Starting from a cultural approach and after the description of these two practices, they are compared with respect to four points: concepts and objects, means and methods, healers' and patients, and effects and expectations. It is argued that these practices have at least five principle points in common: a tendency to objectivation of the underlying framework, a very instrumental way of working, healers' with a high ascribed status, efficacy along the indirect line of symbolic healing, and a comparable way of dealing with unknown and uncontrolled forces. What can these practices learn from each other?